2011
DOI: 10.1128/jcm.00651-11
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Cryptococcus neoformans and Cryptococcus gattii by Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry

Abstract: Compared to DNA sequence analysis, matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) correctly identified 100% of Cryptococcus species, distinguishing the notable pathogens Cryptococcus neoformans and C. gattii. Identification was greatly enhanced by supplementing a commercial spectral library with additional entries to account for subspecies variability.Cryptococcosis is typically a severe infection of the central nervous system characterized by meningoencephalitis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 44 publications
(48 reference statements)
8
49
0
Order By: Relevance
“…ficulties in identification were reported by other studies using the manufacturers' standard databases (9,10,18,19). Good performances were obtained for Cryptococcus by enriching the databases (20,21). Of the 6 Trichosporon isolates tested, 3 isolates of T. mucoides were correctly identified by both systems, but T. asahii, T. inkin, and T. cutaneum posed problems of nonidentification or misidentification as other species of the genus Trichosporon.…”
Section: Discussionmentioning
confidence: 67%
“…ficulties in identification were reported by other studies using the manufacturers' standard databases (9,10,18,19). Good performances were obtained for Cryptococcus by enriching the databases (20,21). Of the 6 Trichosporon isolates tested, 3 isolates of T. mucoides were correctly identified by both systems, but T. asahii, T. inkin, and T. cutaneum posed problems of nonidentification or misidentification as other species of the genus Trichosporon.…”
Section: Discussionmentioning
confidence: 67%
“…(20,29,(35)(36)(37). MALDI-TOF MS has been applied successfully to identify Cryptococcus species, including varieties and hybrids, Candida albicans and non-albicans Candida species, and rare pathogenic yeasts (29,30,(38)(39)(40)(41)(42)(43)(44). Non-Candida species isolates, such as Geotrichum, Galactomyces, Saprochaete, Magnusiomyces, and Trichosporon spp., are underrepresented in the reference library and thus MALDI-TOF MS identification runs were less successful, resulting in low identification rates or failure of reliable analysis (36,45).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of MALDI-TOF MS to identify yeasts and fungi has been demonstrated many times (1,14,23,26,29). In a large comparison, Bader et al found no significant difference between the Saramis and Biotyper databases when identifying yeasts (2).…”
Section: Discussionmentioning
confidence: 99%